2022
DOI: 10.3389/fmed.2022.816843
|View full text |Cite
|
Sign up to set email alerts
|

Triple Therapy in COPD: Can We Welcome the Reduction in Cardiovascular Risk and Mortality?

Abstract: Chronic obstructive pulmonary disease (COPD) is a complex disease which consists in the reduction of the airflow and leads to the disruption of the pulmonary tissue due to a chronic inflammation. The progression of the disease is characterized by an exacerbation of the symptoms and the presence of life-threatening systemic complications, such as stroke and ischemic heart disease, with a progressive decline in lung function which can deeply impact the quality of life. Mortality represents the most important COP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 78 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…But on the other hand, everything can be a risk; it all depends on how someone analyzes the danger, considers the event.” 7 Yet, despite this reality, almost everything in the medical literature is placed spontaneously into the “risk concept” basket. For example, smoking, physical inactivity, poor diet, and air pollution will trigger inflammation and aging; this triggering will lead to cardiovascular diseases with chronic obstructive pulmonary disease (COPD) in various pathophysiological ways; COPD, heart failure, atrial fibrillation, diabetes, pulmonary hypertension, and ischemic heart disease will each turn into a risk factor for the other, and all these risks can be reduced with “triple (inhaler) treatment…” 8 …”
Section: Genomicsmentioning
confidence: 99%
“…But on the other hand, everything can be a risk; it all depends on how someone analyzes the danger, considers the event.” 7 Yet, despite this reality, almost everything in the medical literature is placed spontaneously into the “risk concept” basket. For example, smoking, physical inactivity, poor diet, and air pollution will trigger inflammation and aging; this triggering will lead to cardiovascular diseases with chronic obstructive pulmonary disease (COPD) in various pathophysiological ways; COPD, heart failure, atrial fibrillation, diabetes, pulmonary hypertension, and ischemic heart disease will each turn into a risk factor for the other, and all these risks can be reduced with “triple (inhaler) treatment…” 8 …”
Section: Genomicsmentioning
confidence: 99%
“…2 ICS/LABA/LAMA fixed-dose combinations improve respiratory function, symptoms, health status, and reduce exacerbations compared to dual therapies. 31,32 Triple therapy also demonstrated a significant impact on mortality and frequency of moderate or severe exacerbations compared with LABA/LAMA. 2,33,34 Our observations showed that patients treated with triple therapy remained on triple therapy throughout the study, whereas patient prescribed ICS/LABA were often stepped up to triple therapy.…”
mentioning
confidence: 98%